“Uma mão protetora que os desvie do abismo”: Sociedade Portuguesa de Beneficência de Porto Alegre e seu hospital (1854-1904) - Quevedo, Éverton Reis (Universidade do Vale do Rio dos Sinos, 2016)
The objective of this research is to recover and show the trajectory of the Portuguese Society Charity of Porto Alegre and its largest investment, the Portuguese Beneficent Hospital of Porto Alegre, the point of view of its inclusion in the everydayness of medical and social capital, and even in regional and national community more broadly. The hospital constitutes in a documentary field, with not only a place of healing, but registration, formation and accumulation of knowledge. In this sense, the Portuguese Beneficent Hospital of Porto Alegre has untapped archives that record the institutional routine, adding files to the other memory institutions of Rio Grande do Sul intend, thus visualizing the creation and history of the Portuguese Beneficent Society, using it as a privileged observatory for understanding ethnic mutualism, urban relational context in which it appears (social, economic and family) and the experiences and perceptions of healing, care and charity.
Keywords: Hospital; Beneficência Portuguesa; Saúde pública; Medicina; Porto Alegre; Portuguese Beneficence; Public health; Medicine; ACCNPQ::Ciências Humanas::História